Sistem Informasi Statistik di Koprasi Karya Nugraha dengan Menggunakan Metode OLAP - Fahmi Yusuf; Agus Wahyudin; Elis Khaerunisa (NUANSA INFORMATIKA, 2010)
Statistic information system and strategy have a big role in national development in general especially in  the economic field,it  is used to support  the improvement, efficiency, effectiveness and productivity of government organizations and businesses, such cooperation. At this time, information systems and statistics have been developed, and become an important factor in the process of planning, monitoring, and supervision of the construction, as well as in enhancing the credibility and competitiveness. Therefore, the development of information systems and statistics that is reliably deployed as an integral part in the face of an increasing business competition. Technology OLAP (Online Analytical Processing) offers a solution that needs  a system  to manage and maintain the balance of the elements in the business,it is expected to maintain a stable business processes. OLAP is a flexible data model that  ensures,  respond to changing business requirements needed for effective decision making.